Coulteria lewisiae (Leguminosae: Caesalpinioideae) a new species for Infiernillo region, Mexico - Sotuyo, Solange; Contreras-Jiménez, José Luis (Phytotaxa, 2021)
A new Coulteria species from the seasonally dry forest of Infiernillo region, México is described and illustrated. Coulteria lewisiae, has young leaves sericeous that changes to adpresse tomentose when mature, flowers of 2 cm length (notable in the genus), and a glabrous fruit.